Existence and blow up of solutions of a viscoelastic m(x)-biharmonic equation with logarithmic source term - Gülistan Butakın; Erhan Pişkin (Miskolc Mathematical Notes)
In this paper, we are concerned with a logarithmic nonlinear viscoelastic m(x)